The middle class in macroeconomics and growth theory: A three class neo-Kaleckian - Goodwin model - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
This paper presents a three class growth model with labor market conflict. The classes are workers, a middle management middle class, and a "top" management capitalist class. The model introduces personal income distribution that supplements conventional concerns with functional income distribution. Within such a model, endogenously generated changes in personal income distribution can generate endogenous shifts from profit-led to wage-led regimes and vice-versa. A model of an economy with three classes enables us to consider richer patterns of class conflict because the middle class has shared interests and conflicts with both capitalists and workers. Changes that benefit the middle class do not necessarily increase growth or employment or benefit workers.
urn:nbn:de:101:1-2014031112404
Keywords: E12; O41; O33; 330; Middle class; class conflict; economic growth; income distribution; managerial pay; bargaining power